(untitled) (Journal of the College of Basic Education, 2022)
The research aims to know the effect of the circular house strategy on the achievement and attitude of the fifth grade secondary students in the subject of geography. To achieve this goal, the following null hypotheses were formulated: 1- There are no statistically significant differences at the level (0,05) of the average scores of the experimental group students who study geography by the circular house strategy and the scores of the control group students who study in the usual way in the achievement test. 2- There are no statistically significant differences at the level (0,05) of the average scores of the experimental group who are according geography by the circular house strategy and the average scores of the control group of students who study in the usual way in the direction gauge. The current research is limited to the students of Al-Aqila School for Girls, fifth grade of middle school, in the subject of physical geography - the first semester (2018-2019). The research sample consisted of (60) female students distributed in two classrooms, with (30) female students in the experimental group on which the circular house strategy was applied, and the second (30) control group that studied in the usual way. The results of the current search were : 1- The students of the experimental group outperformed the students of the control group in achievement 2- The students of the experimental group outperformed the students of the control group in the direction gauge in the subject of geography